Long-term Follow-Up and Regeneration of Retinal Pigment Epithelium (RPE) after Tears of the Epithelium in Exudative Age-Related Macular Degeneration (AMD) - Skalicky, Nicolas; Hatz-Wurziger, Katja (Klinische Monatsblätter für Augenheilkunde, 2024)
Background The goals of this study are to evaluate potential long-term visual deterioration associated with retinal pigment epithelial (RPE) tears in patients with neovascular age-related macular degeneration (nAMD) and to find treatment-related and morphological factors that might influence the outcomes.Patients and Methods This retrospective study enrolled 21 eyes of 21 patients from the database of Vista Eye Clinic Binningen, Switzerland, diagnosed with RPE tears, as confirmed by spectral domain optical coherence tomography (SD-OCT), with a minimum follow-up period of 12 months. Treatment history before and after RPE rupture with anti-VEGF therapy, visual acuity, and imaging (SD-OCT) were analyzed and statistically evaluated for possible correlations.Results Mean patient age was 80.5 ± 6.2 years. The mean length of total follow-up was 39.7 ± 13.9 months. The mean pigment epithelial detachment (PED) height increased by 363.8 ± 355.5 µm from the first consultation to 562.8 ± 251.5 µm at the last consultation prior to rupture. Therefore, a higher risk of RPE rupture is implied as a result of an increase in PED height (p = 0.004, n = 14). The mean visual acuity before rupture was 66.2 ± 16.0 letters. Mean visual acuity deteriorated to 60.8 ± 18.6 letters at the first consultation after rupture (p = 0.052, n = 21). A statistically nonsignificant decrease in vision was noted in the follow-up period. After 2 years, the mean BCVA decreased by 10.5 ± 23.7 ETDRS letters (p = 0.23, n = 19). PED characteristics before rupture and amount of anti-VEGF injections after rupture did not affect the visual outcome. None of the 21 patients included in our study showed a visual improvement in the long-term follow-up. RPE atrophy increased significantly from 3.35 ± 2.94 mm2 (baseline) to 6.81 ± 6.25 mm2 over the course of 2 years (p = 0.000 013, n = 20).Conclusions The overall mean vision decrease after rupture was without statistical significance. There was no significant change in BCVA at the 2-year follow-up, independent of the amount of anti-VEGF injections provided. In this study, there was a significant increase in RPE defect over a follow-up of 2 years, implying progression of contraction of RPE and/or macular atrophy.
Keywords: retinal pigment epithelial tears; regeneration of retinal pigment epithelial tears; risk factors for retinal pigment epithelial tears; prognostic factors in retinal pigment epithelial tears